SOCIO ECONOMIC EMPOWERMENT OF WOMEN WORKERS IN CONSTRUCTION INDUSTRY (International Journal of Food and Nutritional Sciences, 2022)
The essence of the living of people is reflected in their social and economic qualities of life. India's unorganised economy consists both semi-skilled and unskilled labourers. Workers in the construction industry are mainly manual labourers. Size of female workers will outweigh male workers. The economic condition of female construction workers is examined in this study using the following variables: occupation, work category, wages, working hours, savings, etc. The researcher has used convenience sampling in this study. Fifty female construction workers from the city of Tirunelveli are the subjects of this research. Secondary data comes from sources such as journals, websites, government notices, and well-structured interview schedules, while primary data is gathered through other ways. The data for this study has been analyzed using SPSS statistics, which includes tests like t- tests, ANOVA, and percentage analyses. According to the research, the majorities of these workers are in their middle years and have a lower literacy rate. The majorities of employees have spouses and live in their own homes as nuclear families. Therefore, the data regarding the financial situation of female construction workers provided by this study is quite relevant.